INVESTIGATION ON THE EFFECTS OF ZINC ON GILLS PEROXIDASE ACTIVITY IN THE FISH, LABEO ROHITA - A. Ashraf; M. Javed; S. Abbas (Journal of Animal and Plant Sciences, 2018)
rd th th Four groups of fish equal in lengths and weights were exposed, separately, to 96-hr LC , 2/3 , 1/4 and 1/5 of LC 50 50 concentrations of zinc for 30 days in the glass aquaria. Another group was kept as control which was not exposed to any metal concentration. After 30-day zinc exposure, the fish from all treatments were sacrificed and their gills isolated for peroxidase enzyme assay. Physico-chemical parameters viz. pH, dissolved oxygen, carbon dioxide, total hardness, calcium, magnesium and total ammonia of the test media were monitored, twice a day. The data were subjected to statistical analyses by following the factorial design. The correlation and regression analyses were also employed to see the statistical relationships among different parameters under study. The results revealed that peroxidase activity was increased significantly in the gills of Labeo rohita after exposure of zinc in all treatments as compared to the control fish -1 gills. The peroxidase activity was measured as 0.353±0.003 UmL in the 96-hr LC metal exposed fish gills while the 50 -1 same was 0.079±0.003 UmL in the control fish. The regression of peroxidase activity on physico-chemical variables of the test media showed significantly positive coefficients on all the variables except dissolved oxygen. carcinogenic also affect adversely the immune system of
Keywords: Labeo rohita; gills; enzyme activity; zinc; sub-lethal.